Legal liability in theory and Constitution of Ukraine - Кучма, Ольга Леонідівна (Київський національний університет імені Тараса Шевченка, 2017)
In the article legal responsibility is analysed in a legal doctrine, judicial practice, intercommunication of tort obligation and tortious liability is examined also. A special attention is paid to the constitutional principles of responsibility and suggestions in relation to perfection of constitutional norm are given. Conception of legal responsibility is investigated in foreign legal literature

У статті аналізується юридична відповідальність у правовій доктрині, розглядаються судова практика, взаємозв’язок деліктного зобов’язання та деліктноївідповідальності,приділяється увага конституційним засадам відповідальності та надаються пропозиції щодо вдосконалення конституційної норми,досліджується концепція юридичної відповідальності у зарубіжній правовій літературі.
Юридична відповідальність у теорії та конституції України
Keywords: юридична відповідальність; обов’язок; примусовий вплив; порушення; компенсація; неустойка; негативний наслідок; legal responsibility; duty; force influence; violation; indemnification; forfeit; negative consequence